Pencegahan Penyalahgunaan Suplemen dan Herbal dengan Penyuluhan di Poliklinik Rawat Jalan RS Harapan Sehati, Bogor: indonesia - Ismyama, Dian Farida; Kusuma , Ema Nillafita Putri; Sa’adah, Aas; Hermawati , Ema (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Public awareness of the importance of health is increasingly developing towards a better direction. One method is by consuming supplements and herbal medicines to increase the body's resistance to avoid certain diseases. The consumption of safe, high-quality and useful herbal supplements and medicines needs to be cultivated and preserved by the community. Therefore, community service was carried out which consisted of 3 stages of activities, namely distributing questionnaires before counseling, counseling, and distributing questionnaires after counseling to see whether there was an influence of counseling on knowledge. The aim of this activity is to increase public awareness of the misuse and wrong use of supplements and herbal medicines. Community service was carried out at Harapan Sehati Hospital in the Bojonggede area, Bogor Regency with a total of 30 participants.   are used for the counselling. Data were collected using a questionnaire consisting of demographics, knowledge and behavior of participants regarding the use of supplements and herbal medicines. Data processing uses descriptive analysis methods, and the non-parametric Wilcoxon Signed Rank Test. The majority of participants were women (83.3%) and aged 17-25 years (43.3%). As many as 66.7% of participants were college graduates and 96.7% worked as private employees. The percentage of participants who had good knowledge about supplements and traditional medicine before (pre) counseling was 43.3%. Good knowledge becomes 80% after (post) counseling. The data shows a p-value of 0.001 (<0.05), which means there is an influence of counseling, or there is a significant difference between knowledge before and after being given education. It can be concluded that this series of activities is effective in increasing knowledge about the use of supplements and herbal medicines, so it is hoped that it can prevent misuse.